Rethinking on the methodology for assessing global water and food challenges. Issue 2 (3rd March 2020) - Kumar, M. Dinesh; Bassi, Nitin; Singh, O. P.
ABSTRACT: The article delinks food security challenges from the challenge of supplying water to meet the needs of the industrial, livestock, domestic and environmental sectors to analyze the food security and water management challenges of individual nations. For this, three indices are developed: the water adequacy index, water-land index and water-land-pasture index. Their values are computed for 172 countries. The analysis suggests that the criteria for assessing the magnitude of food insecurity and water scarcity problems should include agricultural land, particularly cultivated land and pastureland, along with renewable water.